Akceptacja idei odpowiedzialności za zdrowie własne i innych przez kandydatów do zawodu nauczycielskiego - wyzwanie w kształceniu wyższym = Acceptance of the idea of responsibility for one`s own and others` health by candidates for the teaching profession - a challenge in higher education - Kołecka, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the research was to answer 3 research questions. The first one concerned the source of information about the idea of responsibility for one?s own and others? (i.e. students?) health among candidates for the teaching profession. The second was related to their acceptance of this idea. The third concerned the willingness to know the respondents? opinions on special classes dedicated to candidates for the teaching profession in terms of the sense of responsibility being researched. 211 students of pedagogical faculties of universities in the Lubuskie Voivodeship participated in the study. An original questionnaire was used concerning: the opinion on the assumption of responsibility for one?s own health and that of others by candidates for the teaching profession.
Keywords: edukacja zdrowotna; akceptacja idei odpowiedzialności; health education; acceptance of the idea of responsibility